The five-coordinate cadmium halide bis(diethyldithiocarbamate) complexes [PPh4][Cd(S2CNEt2)2Cl] and [PPh4][Cd(S2CNEt2)2Br] - Baggio, R. (1996)
The title compounds, tetraphenylphosphonium chlorobis(diethyldithiocarbamato-S,S)cadmium(II), (C24H20P)-[CdCl(C5H10NS 2)2], (1), and tetraphenylphosphonium bromobis(diethyldithiocarbamato-S,S)cadmium(II), (C24-H20P)[CdBr(C5H10NS 2)2], (2), are isomorphous. The compexes are mononuclear with coordination spheres of the types S4Cl and S4Br, respectively. The central Cd atom is linked to four S atoms and two bidentate dithiocarbamate ligands and to the halide atom. The resulting Cd-atom coordination geometry is halfway between trigonal bipyrimidal and square pyramidal. Principal dimensions include: Cd-S 2.573 (1)-2.682 (1) in (1) and 2.571 (3)-2.736 (2) Å in (2); Cd-Cl and Cd-Br 2.462 (1) and 2.626 (1) Å, respectively.